ANALISIS KINERJA SIMPANG BERSINYAL PADA SIMPANG LAKARSANTRI – DRIYOREJO MENGGUNAKAN METODE - Sani, Naufal Yafi; Hartatik, Nurani; Fatmawati, Laily Endah (LPPM Universitas Bina Bangsa, 2023)
In this modern era, the increasing development of science and technology has led to an increase in human activity which is followed by an increase in vehicle capacity and a decrease in pedestrians. So transportation needs will increase. In Surabaya, the need for transportation has become a primary need for very dense city residents and the situation at the Lakarsantri – Driyorejo intersection uses 3 signal phases with the 311 type intersection, where if one arm of the intersection is in the green phase, the other two phases are in the red phase and vice versa. This is very busy during peak hours such as in the morning, namely at 07.00-08.00, that time is usually busy due to the time of going to work, school and so on and during the day, namely at 12.00-13.00, office break time, school time. Used in this research is the 1997 Indonesian Road Capacity Manual (MKJI 1997). This research carried out traffic surveillance on the number of vehicles passing, intersection capacity, and the degree of saturation. From the research results, it was found that the highest traffic volume at the intersection of Lakarsantri – Driyorejo, Surabaya City occurred on Thursday at 17.00-18.00 WIB, Jalan Lakarsantri (West) was 630 pcu/hour, Jalan Menganti (East) was 473 pcu/hour, and Jalan Driyorejo was 657 pcu/hour. And it has an average degree of saturation of 0.95.